Business Vulnerability and Credit Access for Agriculture-Based Micro and Small Women Entrepreneurs - Dewi Ratna Sjari Martokoesoemo; Bonar M. Sinaga; Nunung Kusnadi; Yusman Syaukat (Economics and Finance in Indonesia, 2020)
Micro and Small Industries (MSIs) constitute the largest share of Indonesia’s manufacturing sector and play an important role in providing employment opportunities and value-added creation. However, their business sustainability and scaling up are often hindered by various factors, one of which is access to credit. The subsidized loan scheme provided by the government, namely People’s Business Credit (KUR), appears to be insufficiently attractive to entrepreneurs, especially to Micro and Small Women Entrepreneurs (MSWEs). Employing a logit regression method and utilizing the BPS-Statistics Indonesia’s 2015 MSI survey data, this study aims to investigate factors affecting MSWEs’ decision to apply for bank loans and factors contributing to the approval of their credit applications by banks. The results show that MSWEs have low participation in credit borrowing, partially due to business vulnerability and self-rationing attitude, while credit application rejection is caused mainly by banks’ conservative approach to MSWEs. Practical implications of the findings are discussed.